2000
DOI: 10.1044/1058-0360.0901.03
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Educational Materials for Clients With Cleft Lip/Palate and Their Families

Abstract: Educational materials for clients with cleft lip/palate and their families and materials for the general public produced by the American Speech-Language-Hearing Association were analyzed for readability. The SMOG Grading Formula, a simple, fast procedure for predicting grade-level difficulty of written material, and the Fry index of readability, a more lengthy measure of readability, were used to analyze 30 publications. Reading levels were computed, and results ranged from elementary to college level. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…Our results are in line with previous studies that have calculated the readability index of English-language texts in audiology and otolaryngology and found most measures were beyond the level recommended for the average patient (Atcherson et al, 2011;Kahn & Pannbacker, 2000;Kelly-Campbell et al, 2012;Laplante-Lévesque & Thorén, 2015;Nair & Cienkowski, 2010). In one recent study, researchers examined self-reported hearing disability measures in English and concluded, using three formulae, the range of readability for the HHIE was sixth to 9.6th grade and the range for the APHAB was sixth to 7.8th grade (KellyCampbell et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in line with previous studies that have calculated the readability index of English-language texts in audiology and otolaryngology and found most measures were beyond the level recommended for the average patient (Atcherson et al, 2011;Kahn & Pannbacker, 2000;Kelly-Campbell et al, 2012;Laplante-Lévesque & Thorén, 2015;Nair & Cienkowski, 2010). In one recent study, researchers examined self-reported hearing disability measures in English and concluded, using three formulae, the range of readability for the HHIE was sixth to 9.6th grade and the range for the APHAB was sixth to 7.8th grade (KellyCampbell et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…It is recommended that health-related materials for the general public should be written at or below a fifth-grade level, or age 10-11 years (Doak, Doak, & Root, 1996;Weiss & Coyne, 1997). However, a number of previous studies have shown that widely used English-language materials in audiology and otolaryngology are beyond the recommended level (Atcherson, Zraick, & Brasseux, 2011;Kahn & Pannbacker, 2000;Kelly-Campbell, Atcherson, Zimmerman, & Zraick, 2012;Laplante-Lévesque & Thorén, 2015;Nair & Cienkowski, 2010).…”
Section: Results: Readability Calculations Agreed With Previous Studimentioning
confidence: 99%
“…The limited research carried out in speech-language pathology and audiology is striking given that the IOM (2004) identified speaking and listening as areas in need of improvement in health literacy research and intervention. Two studies relevant to these professions were identified, which focused on the readability of educational materials for clients with cleft lip and/or palate and their families, as well as the effects of reader and text variables on understanding of health information in adults (Harris, Fleming & McDougall, 2003;Kahn & Pannbacker, 2000). These studies suggest that individuals with communication difficulties and their carers are at an even greater risk of not understanding written materials.…”
Section: Health Literacy: a Backgroundmentioning
confidence: 99%
“…5, 2012 In a written tutorial on health literacy and the role of the speech-language pathologist, 18 it was reported that the speech-language pathology literature contains few studies related to health literacy. Available studies have examined the readability of cleft palate educational materials, 19 text and reader variables related to understanding health information, 20 and factors that influence utilization of speech-language pathology services by older adults. 21 Additionally, some recent studies have examined ways to modify aphasia consumer materials 22,23 and one study examined readability of patient information leaflets in a speech and language therapy department.…”
Section: Level and Definition Key Abilities Associated With Levelmentioning
confidence: 99%